Love And Friendship Reflected In The Novels Of Ahmad Fuadi's "The Land Of Five Towers"(2011), Andrea Hirata's "The Rainbow Troops" (2009) And Andrea Hirata's"Edensor" (2011) - JAMIATI, Sri, Dr. Dewi Candraningrung, Dr. Abdillah Nugroho, M. Hum (2015)
The objectives of the research are 1) to describe how love is reflected in the novels of Ahmad Fuadi's The Land of Five Towers, Andrea Hirata's The Rainbow Troops, and Andrea Hirata's Edensor, 2) to describe how friendship is reflected in the novels of Ahmad Fuadi's The Land of Five Towers, Andrea Hirata's The Rainbow Troops, and Andrea Hirata's Edensor. The type of the research that is used by the researcher is qualitative research. In this study, the researcher wants to describe systematically, factually, and accurately an interest of one of the extrinsic factor of novel that is love and friendship reflected in the novels. The researcher uses the descriptive method to analyze love and friendship. The results of the research showed that love in the novels are three types of love can be noticed. They are companionate love, infatuation love, and romantic love. The elements involved in the forms of love above are passion, intimacy, and commitment. Friendship in the novels is based on four values, solid foundation; communication; respect differences; and enjoy togetherness. They are reflected through analysis of theme, characters, and setting. A good friendship is beneficial in all areas of their life